The Education Funding Crisis: How Is The Lack Of Budget Affevtinh Facilities , Cuciculum and Academic Achievement - A. Erni Ratna Dewi; Amalia Tasya; Rosmaria Rosmaria; Sarkowi Sarkowi (Journal of Pedagogi, 2025)
The education funding crisis has a significant impact on the quality of facilities, curriculum innovation, and student achievement. Budget shortfalls result in the degradation of physical facilities such as damaged classrooms and limited access to technology, which directly reduce student motivation and participation in the learning process. In addition, the funding crisis exacerbates educational inequalities between well-equipped and under-funded schools, widening the socio-economic gap. Lack of funding also hampers the development of innovative curricula, such as STEM-based learning and digital literacy, which are increasingly needed in the era of globalization and the industrial revolution 4.0. Without adequate investment, efforts to modernize the curriculum and improve teacher skills are severely limited, limiting students' readiness to face the challenges of the future world of work. This decline in the quality of education results in lower academic achievement and exacerbates social inequities, where students from low-income backgrounds find it more difficult to improve their social status. Therefore, solutions to the education funding crisis require greater budget allocation, infrastructure renewal, and adaptive curriculum development to reduce social inequality and support sustainable economic growth.